Digitalization and Firm Performance in ASTRA: The Mediating Role of Differentiation Strategy - Maulana, Aprizal; Novianto , Irfan; Iskandarsyah , M. Sultan; Khairal Abdullah , Tengku Mohd (Ridwan Institute, 2024)
Digitalization has emerged as a key factor in achieving sustainable performance. This is shown by the number of companies that utilize digital technology and related research to increase competitive advantage. The purpose of this study is to examine the relationship between digitalization mediated by strategic differentiation and firm performance. The research methodology used in this research is quantitative method. The target of this research is companies in the ASTRA with a research sample consisting of 80 respondents. The findings show that digitalization has been proven to have an impact on firm performance, strategic differentiation has been proven to have an impact on firm performance, and strategic differentiation is able to mediate between digitalization and firm performance. Practical implication: Digitalization allows companies to implement differentiation strategies more effectively. By adopting the right digital technology, companies can create unique, personalized, and value-added products or services for customers. These advantages can differentiate the company from competitors and provide a strong attraction for customers, which in turn can improve the firm performance. This report is derived from research conducted at the middle and top management levels in several companies in the ASTRA.